Cecilia, Antonio e Eu : literatura, memória e fotografia na (re)construção da história de uma família italiana no RS - Tremea, Rosane (2024)
This dissertation consists of two parts. The first part, entitled “Cecilia, Antonio and I” presents a creative text reconstructing the story of two Italian immigrants in Rio Grande do Sul, Brazil. The narrative creates a biography for the couple, adding fiction to a few documents and photographs. Departing from the documents and images, not only is the trajectory of Cecilia and Antonio told, but also a little of the history of Italian immigration to RS in the 19th century. It also deals with a great-granddaughter's search for family origins and memories in her own country and in Italy, using autobiography and autofiction. The second part consists of a literary essay. In the essay, the author reflects on the process of constructing the creative text based on works read during the Master's degree. Inspiration and references were sought from them, in addition to analyzing the narrators and the use of photography, in books whose authors portray their own families